2021
DOI: 10.1186/s12302-021-00517-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in handwashing and hygiene product usage patterns in Korea before and after the outbreak of COVID-19

Abstract: Background The World Health Organization declared COVID-19, the disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), a global pandemic on March 11, 2020. Non-pharmaceutical interventions such as social distancing, handwashing, using hand sanitizer, and wearing facial masks are recommended as the first line of protection against COVID-19. Encouraging hand hygiene may be one of the most cost-effective means of reducing the global burden of disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
1
11
0
2
Order By: Relevance
“…Hygiene can disrupt microbiota diversity ( 387 389 ), and a positive correlation has been found between microbiota dysbiosis and the increase of autoimmune conditions such as IBD ( 390 392 ) and SLE ( 393 397 ). This concern is escalating due to the current COVID-19 pandemic that witnessed a dramatic increase in hygiene practices including the use of detergents and disinfectants ( 398 400 ). In fact, these control measures may have long-term consequences on the human microbiome ( 401 , 402 ).…”
Section: Hygiene As An Environment Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Hygiene can disrupt microbiota diversity ( 387 389 ), and a positive correlation has been found between microbiota dysbiosis and the increase of autoimmune conditions such as IBD ( 390 392 ) and SLE ( 393 397 ). This concern is escalating due to the current COVID-19 pandemic that witnessed a dramatic increase in hygiene practices including the use of detergents and disinfectants ( 398 400 ). In fact, these control measures may have long-term consequences on the human microbiome ( 401 , 402 ).…”
Section: Hygiene As An Environment Factormentioning
confidence: 99%
“…current COVID-19 pandemic that witnessed a dramatic increase in hygiene practices including the use of detergents and disinfectants (398)(399)(400). In fact, these control measures may have long-term consequences on the human microbiome (401,402).…”
mentioning
confidence: 99%
“…The presence of such high levels of isothiazolinone in wastewater treatment plants can be attributed to the COVID-19 pandemic situation, during which a much larger amount of cleaning (disinfectants, sanitizers, detergents, and other cleaning products) and personal care products (hand soap, body wash, cleaning gel, and shampoo) was used [28,29]. After the use of products containing biocides (personal care products, cosmetics, detergents) as well as their use to remove biofilm deposited on pipes, a higher amount of biocide is discharged with domestic wastewater into the sewer network, reaching its end in WWTPs.…”
Section: Concentration Of Biocide In Wastewater Samplesmentioning
confidence: 99%
“…Their widespread uses and the improper disposal of the waste that contains such compounds in their chemical formulation could be the principal sources for the occurrence of biocides in surface waters. Since biocides have shown toxicity on aquatic organisms (Table S7), their presence at high levels in surface waters may present adverse effects on aquatic biota, the most common being slowing or stopping cellular growing [28]. Moreover, potential health hazards of these organic pollutants for human health by consuming aquatic organisms is not to be neglected, as recent studies suggested a potential cytotoxicity effect on human liver and neuronal cell lines [30][31][32].…”
Section: Concentration Of Biocide In Riverine Environmentsmentioning
confidence: 99%
“…Failure of water treatment systems in inactivating pathogens has resulted in outbreaks of many waterborne diseases and illnesses. Disinfectants are the best option for eradicating microbes in water treatment systems and other fields (aquaculture, agriculture, domestic purposes, and health care centres) (Holm et al 2019 ; Yun et al 2020 ; Choi et al 2021 ; Huang et al 2021 ). Different kinds of disinfectants were commercially available (totally 131 household products) for use (Goh et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%